Detoxification Processes from Vanadate at the Root Apoplasm Activated by Caffeic and Polygalacturonic Acids - Garau, Giovanni; Palma, Amedeo; Lauro, Gian Paolo; Mele, Elena; Senette, Caterina; Manunza, Bruno; Deiana, Salvatore (PLOS ONE, 2015)
In the root apoplasm, V(V) and V(IV) toxicity can be alleviated through redox and complexation reactions involving phenolic substances and the polyuronic components. In such context we report the role of polygalacturonic acid (PGA) on the reducing activity of caffeic acid (CAF) towards V(V). The redox reaction was particularly effective at pH 2.8 leading to the formation of oxidation products with redox activity towards V(V). An o-quinone was identified as the first product of the reaction which is further involved in the formation of CAF dimers. At pH ≥ 3.6 the redox activity decreased and a yield in V(IV) equal to 38, 31, 21 and 14% was found at pH 3.6, 4.0. 5.0 and 6.0 respectively compared with that obtained at pH 2.8. The redox reaction was faster in the presence of PGA and a higher yield of V(IV) was found in the 4.0–6.0 pH range with respect to the CAF-V(V) binary system. The higher efficiency of the redox reaction in the presence of PGA was related with the ability of PGA to bind V(IV). The biological significance of the redox reaction between CAF and V(V), as well as the role of PGA in such reaction, was established “in vivo” using triticale plants. Results showed that PGA reduced significantly the phytotoxic effects of the V(V)-CAF system.